Change in incidence of hip fracture in Gwangju City and Jeonnam Province, Korea, over 20 years. Issue 1 (December 2015) - Park, Kyung-Soon; Woo, Seong-Hwan; Park, Won-Ju; Rowe, Sung-Man; Yoon, Taek-Rim
Abstract Summary This study determined the incidence of hip fractures in Gwangju city and Jeonnam province of Korea in 2011 and compared it with the rates in the same area in 1991 and 2001. Introduction This study determined the incidence of hip fracture in Gwangju city and Jeonnam province in Korea in 2011 and compared it with the rates in the same area in 1991 and 2001, with the aim of identifying any changes in 2011. Methods Korea Health Insurance Review Agency patient data from Gwangju city and Jeonnam province for the period 2011 January 1 to December 31 was analyzed. All claims and records of patients ≥50 years of age with a diagnosis of fracture of the neck of the femur, pertrochanteric fracture, and hip fracture-related surgeries including open reduction and internal fixation, closed reduction and osteosynthesis, total hip replacement, or bipolar hemiarthroplasty were analyzed. Population figures were obtained from the Korea National Statistical Office. Age- and sex-specific annual incidences were calculated. The 2011 data was compared with published data from 1991 to 2001. Results There were 1590 hip fractures in 2011, representing a crude incidence of 14.0/10, 000. The incidence was 9.7/10, 000 in males and 17.5/10, 000 in females. The number of hip fractures and fracture incidence was 247 and 3.3/10, 000 in 1991 and 1152 and 13.3/10, 000 in 2001, respectively. There was a fourfold increase of fracture incidence between 1991 and 2001. Thereafter, the number of fractures increased only by 5.2 %. However, the number of arthroplasties done increased significantly. Conclusions The incidence of fractures increased considerably between 1991 and 2001, with less increase in the ensuing 10 years.